“Speaking Pictures”: Ways of Seeing and Reading in English Renaissance Culture - Szőnyi, György E. (Studia Anglica Posnaniensia, 2018)
Neither in Antiquity nor in the Middle Ages could literary theory settle the debate about the primacy of inspiration or imitation, Plato or Aristotle. It was in the Renaissance that serious efforts were made to reconcile the two theories, and one of the best syntheses came from England. Philosophical and aesthetical syncretism between Plato and Aristotle makes Sidney’s Defense of Poesie a non-dogmatic and particularly inspiring foundation for English literary theory. Also, Philip Sidney’s notion of “speaking pictures” needs to be revisited, in view of the ontology and epistemology of art, as a ground-breaking model for understanding the multimediality of cultural representations. The first part of the following essay is devoted to this. Furthermore, it will be examined how Sidney’s visual poetics influenced and at the same time represented emblematic ways of seeing and thinking in Elizabethan culture. These are particularly conspicuous in the influence of emblem theory in England and in Renaissance literary practice related to that. In the final section I intend to show that Shakespeare’s intriguing, although implicit, poetics is a telling example of how Renaissance visual culture enabled a model that put equal stress on inspiration and imitation, and also on the part of the audience, whose imagination had (and still has) to work in cooperation with the author’s intention.